3D printed breathable mould steel: Small micrometer-sized, interconnected pores by creatively introducing foaming agent to additive manufacturing. (5th May 2019) - Zeng, G.H.; Song, T.; Dai, Y.H.; Tang, H.P.; Yan, M.
Abstract: Additive manufacturing & 3D printing has almost no limitation in realizing any geometry due to its layer-by-layer manufacturing manner, while producing small-sized, interconnected pores is one of its major challenges. In this study, we report that, by creatively combining additive manufacturing with foaming agent, interconnected pores (~26 vol.% porosity) with pore size of 2–30 μm have been successfully achieved. One of the most important applications of such unique structure is for developing the so-called breathable mould steel. Breathability is rather demanding for the mould industry, since it is capable to eliminate the trapped, detrimental gas during injection moulding and therefore much improve the quality of as-injected parts. It will be revealed by the study that, due to a good selection of the foaming agent (i.e. CrN x ), the as-printed breathable steel has a great combination of compressive strength (~1.3 GPa), strain (~26%), microhardness (~360 HV) and corrosion resistance, along with sufficient breathability. These mechanical properties are even superior to the commercial PM-35 breathable steel. Based on detailed microstructural characterization, the affecting factors to the pore forming are studied, and the importance of the novel approach developed by the current study has been addressed. Graphical abstract: Unlabelled Image Highlights: 3D printed breathable steel with small and interconnected pores Selective laser melting plus foaming agent enabled controlled porosity Breathable steel with excellent mechanical property and corrosion resistance